1988
DOI: 10.1038/332083a0
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine generation and requirement of BSF-2/IL-6 for human multiple myelomas

Abstract: Human B cell stimulatory factor 2 (BSF-2) was originally characterized and isolated as a T cell-derived factor that caused the terminal maturation of activated B cells to immunoglobulin-producing cells. Molecular cloning of the complementary DNA predicts that BSF-2 is a protein of relative molecular mass (Mr) 26,000 similar or identical to interferon beta 2, hybridoma plasmacytoma growth factor and hepatocyte stimulating factor. IL-6 has been proposed as a name for this molecule. It is now known that BSF-2 has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
669
2
8

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,549 publications
(695 citation statements)
references
References 22 publications
16
669
2
8
Order By: Relevance
“…Berdel et al (1988Berdel et al ( , 1989 reported evidence suggesting that haematopoietic growth factors, such as IL-3, GM-CSF and G-CSF, can stimulate the growth of clonogenic cells in some human non-haematopoietic malignant cell lines derived from colorectal and bladder carcinomas in vitro. Similar data also exist for IL-6, which exerts a growth-enhancing effect on nonhaematopoietic tumours and has also been observed in myelomas (Kawano et al, 1988) and renal carcinoma cells (Miki et al, 1989). It has also been reported that GM-CSF can stimulate the proliferation of osteogenic sarcoma and breast cancer cell lines (Dedhar et al, 1988).…”
Section: Discussionsupporting
confidence: 73%
“…Berdel et al (1988Berdel et al ( , 1989 reported evidence suggesting that haematopoietic growth factors, such as IL-3, GM-CSF and G-CSF, can stimulate the growth of clonogenic cells in some human non-haematopoietic malignant cell lines derived from colorectal and bladder carcinomas in vitro. Similar data also exist for IL-6, which exerts a growth-enhancing effect on nonhaematopoietic tumours and has also been observed in myelomas (Kawano et al, 1988) and renal carcinoma cells (Miki et al, 1989). It has also been reported that GM-CSF can stimulate the proliferation of osteogenic sarcoma and breast cancer cell lines (Dedhar et al, 1988).…”
Section: Discussionsupporting
confidence: 73%
“…[4][5][6][7][13][14][15] The studies in this report extend these earlier observations by investigating patients with MGUS using highly sensitive molecular techniques to detect cytokine expression. Furthermore, the above studies suggest a rational mechanism for the progression from MGUS to active myeloma.…”
Section: Tablesupporting
confidence: 62%
“…The IL-1␤ and IL-6 expression studies from unsorted and sorted monoclonal plasma cells from patients with MGUS and myeloma in this report taken in conjunction with previously reported observations suggest that both autocrine and paracrine mechanisms of IL-6 production may be operational in the pathogenesis of myeloma. 4,[13][14][15] Our data demonstrate that monoclonal plasma cells from the majority of myeloma patients with active disease manifested by a high labeling index can express IL-6 mRNA in an autocrine fashion. Hata et al 5 detected IL-6 mRNA by RT/PCR in purified plasma cells from myeloma patients as well and also demonstrated that these CD38 + myeloma cells expressed intermediate levels of CD45.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…MM cells (MMC) are dependent on several growth factors and cytokines, produced by the MMC themselves or by the BM microenvironment. Besides the well-known MMC factors, interleukin-6 (IL-6) (Kawano et al, 1988;Klein et al, 1989) and insulin-like growth factor-1 (IGF-1) (Georgii-Hemming et al, 1996;Jelinek et al, 1997;Ferlin et al, 2000), an increasing number of additional factors are being identified, providing novel therapeutic targets for myeloma (Klein et al, 2003).…”
Section: Introductionmentioning
confidence: 99%